Trade patterns and endogenous institutions: Global evidence - Richard Frensch; Roman Horváth; Stephan Huber (Institut für Ost- und Südosteuropaforschung (IOS), 2016)
We propose a novel way to measure the rule of law intensity of exports at the goods level based on nearly 100 million disaggregated bilateral trade flows around the globe. We categorise goods into three groups: fragmented, primary and other. The theoretical literature on holdup problems connected to incomplete or incompletely enforceable contracts or property rights predicts that goods resulting from fragmented production processes should be the most rule of law intensive. However, we find that the rule of law intensity of other goods is, on average, only slightly lower than that of fragmented goods. We examine how exogenous variation in countries trade patterns influences the quality of institutions. Our regressions show that trade flows generated by fragmented and other processes of production improve rule of law, while trade flows generated by primary production do not.
urn:nbn:de:101:1-201607265025
Keywords: C83; D91; E21; 330; trade patterns; rule of law